Quarter-sweep iterative method for second kind linear fredholm integral equations - Mohana Sundaram Muthuvalu (Tanjong Malim, 2010)
Quarter-sweep iterative method for second kind linear fredholm integral equations by Mohana Sundaram Muthuvalu